New substitute name for the genus Mistaria Medler, 1988 (Hemiptera: Fulgoromorpha: Flatidae) - Yang, Wei-Cheng; Chen, Xiang-Sheng (Zootaxa, 2015)
The African planthopper species Flata crassivenosa Karsch, 1890 was described by Karsch (1890) from Congo. Later, Melichar (1901) placed this species in the genus Walkeria Melichar, 1901 together with Flata radiata Distant, 1892 however, that name appeared to be preoccupied and Kirkaldy (1906) proposed for it a new replacement name Eumelicharia Kirkaldy, 1906 and designated Flata radiata as the type species. Medler (1988) in his paper on Flatidae from Taï Forest (Côte d’Ivoire) established a new genus Mistaria Medler, 1988 with Flata crassivenosa Karsch, 1890 as its type species and proposed that the new genus can be separated from Eumelicharia by its development of a strong uniform network of crossveins. However, the genus name Mistaria is preoccupied and was initially introduced by Lehtinen (1967) for a spider Agelena leucopyga Pavesi, 1883 (Arachnida: Araneae: Agelenidae), as the type species, from East Africa. Thus, the genus Mistaria Medler, 1988 is a junior homonym of the genus Mistaria Lehtinen, 1967. According to Article 60 of the International Code of Zoological Nomenclature (ICZN 1999), we propose the new replacement name Neomistaria nom. nov. for Mistaria Medler, 1988. The resulting nomenclatural changes are summarized below.